Religious Legitimacy in Realizing Harmony in Indonesia - Yunika Sari; Paulus Sunu Sukmono Wasi (Parahyangan Catholic University, 2022)
This study aims to discuss religious harmony as a form of religious tolerance seen from the perspective of religions. The research methodology is qualitative, library research that uses a descriptive approach to explain religious harmony. The discussion of this research includes the notion of religious harmony, the principle of the trilogy of religious harmony, concepts, methods, guidelines and quality of religious harmony, the legal basis and objectives of religious harmony, the supporting and inhibiting factors for the occurrence of religious harmony and religious harmony from a spiritual perspective. This study concludes that religious harmony is a condition of interaction between individuals/groups in which various religious groups can live together without reducing the fundamental rights of each to carry out their religious obligations.